A selective fluorescent sensor for Zn2+ based on aggregation-induced emission (AIE) activity and metal chelating ability of bis(2-pyridyl)diphenylethylene. Issue 36 (23rd August 2016) - Gabr, Moustafa T.; Pigge, F. Christopher
Abstract : A bis(2-pyridyl)tetraarylethylene exhibits selective "turn-on" fluorescence enhancement in the presence of Zn 2+ ions. Abstract : Polypyridyl ethylenes have been prepared as heterocyclic analogues of tetraphenylethylene. In addition to conventional AIE effects, a derivative possessing a 1, 1-bis(2-pyridyl)ethylene fragment displays Zn 2+ -selective enhanced fluorescence in aqueous solution, in contrast to the behavior of isomeric bis(3- and 4-pyridyl)ethylenes. The Zn 2+ -sensing capability of this material is attributed to formation of chelated Zn 2+ -bis(pyridyl) complexes and is supported by the X-ray crystal structure of a bis(2-pyridyl)ethylene-Zn(OAc)2 complex.